2012
DOI: 10.1093/humrep/des291
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β stimulates the secretion of thymic stromal lymphopoietin (TSLP) from endometrioma stromal cells: possible involvement of TSLP in endometriosis

Abstract: study question: Is thymic stromal lymphopoietin (TSLP) involved in the pathophysiology of endometriosis? summary answer: TSLP is up-regulated by interleukin (IL)-1b and may be involved in the development of endometriosis. what is known already: Endometriosis is a chronic inflammatory disease in which the Th2 immune response is activated and has been suggested to promote the disease. TSLP is a master cytokine that drive Th2 immune response. study design, size, duration: A laboratory study. participants/material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 52 publications
4
31
2
Order By: Relevance
“…34 Previously, our group demonstrated for the first time the presence of Th17 in endometriosis lesion. The proportion of Th1 was significantly lower in endometriosis lesions than in endometrium, whereas the proportion of Th17 was significantly higher in endometriosis lesions than in endometrium.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…34 Previously, our group demonstrated for the first time the presence of Th17 in endometriosis lesion. The proportion of Th1 was significantly lower in endometriosis lesions than in endometrium, whereas the proportion of Th17 was significantly higher in endometriosis lesions than in endometrium.…”
Section: Discussionmentioning
confidence: 91%
“…The age of patients in Group C (33.5, 27-43) was not significantly different from that of patients in Group D (31,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Six women were in the proliferative phase and four were in the secretory phase (Group C), and four women were in proliferative phase and six were in secretory phase (Group D) at the time of sample collection.…”
Section: Subjects and Samplesmentioning
confidence: 87%
“…In the endometriosis lesion, the frequency of Th1 cells is lower than in normal endometrium . Furthermore, Th2 cytokines, such as IL‐4, IL‐10, and TSLP, have been shown to contribute to disease progression. Studies of peripheral blood, however, have revealed a higher Th1/Th2 cytokine ratio and Th1 cell frequency in endometriosis patients compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IL-1β may also contribute to the Th2 immune response by improving the secretion of thymic stromal lymphopoietin. 38 Therefore, in an inflammatory ESC were stimulated with IL-1β (1 ng/mL) or vehicle (medium) for 24 h, or were pre-incubated with lipoxin (LX)A 4 alone for 24 h, or pre-incubated with LXA 4 (100 nmol/L, 30 min) and stimulated with IL-1β (1 ng/mL, 24 h). These experiments were performed three times using different batches of cells, and data are given as mean ± SEM.…”
Section: Discussionmentioning
confidence: 99%